OVERVIEW OF LEUKOCYTE COUNTS IN PULMONARY TUBERCULOSIS PATIENTS HOSPITALIZED RSU BUNDA THAMRIN - Siahaan, Maniur A; Zebua, Winda Irawati; Sipayung, Apriska Dewi (Jurnal Analis Laboratorium Medik, 2024)
Tuberculosis (TB) is a disease caused by mycobacterium tuberculosis. TB can be transmitted to onther through Saliva when someone sneezes or coughs, then through breathing. This disease is difficult to control worldwide. TB bacteria move from the lungs and spread through the blood to other parts of the body. These diseases damage bones, damage the liver, kidneys, heart and other organs, weaken the immune system, cause loss of consciousness, and if left untreated can result in death. The researhc method used in this study is descriptive, which aims to determine the Leukocyte Description in Pulmonary Tuberculosis patients. This study uses an autohematology analyzer to examine the number of leukocyte cells. This study was conducted at Bunda Thamrin Hospital Medan from May To Juni 2024 where the samples used were 15 blood samples from pulmonary tuberculosis patients. The population in this study were all patients who were clinically diagnosed with tuberculosis by doctors who were hospitalized at Bunda Thamrin Hospital, Medan, in May- June 2024 to conduct tuberculosis examinations totaling 15 people. The sampel in this study used the total sampling technique. The results of the examination found that patients wit decreased white blood cell counts (leukopenia) were 3 people (20%), while 6 patients experience d increased leukocytes (leukocytosis) (40%), and 6 people had normal leukocytes (40%) from 15 blood samples of pulmonary tuberkulosis patients. It is hoped that further research Will increase the sample to obtain a more optimal picture of leukocytes results.